2015
DOI: 10.1186/s13075-015-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum hyaluronic acid concentration predicts the progression of joint space narrowing in normal knees and established knee osteoarthritis – a five-year prospective cohort study

Abstract: IntroductionSerum hyaluronic acid (sHA) is a serum biomarker for knee osteoarthritis (OA). Although sHA concentration is elevated in patients with knee OA, the relationship between serum concentration and disease progression remains unclear. We examined the relationship between sHA concentration and radiographic progression of knee OA in a cohort of individuals followed for 5 years.MethodsWe prospectively enrolled 444 individuals and measured their sHA concentrations at baseline. Anterior-posterior weight bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…These results add to the growing evidence that the clinical course of OA may be associated with systemic inflammation (2,5,10). Several serum biomarkers are known to be correlated with OA incidence and progression and have thus been proposed as diagnostic and prognostic markers for knee OA (28)(29)(30)(31). Serum hyaluronic acid concentration was found to be positively associated with progression of Kellgren/Lawrence grade in knees with and without OA (31).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These results add to the growing evidence that the clinical course of OA may be associated with systemic inflammation (2,5,10). Several serum biomarkers are known to be correlated with OA incidence and progression and have thus been proposed as diagnostic and prognostic markers for knee OA (28)(29)(30)(31). Serum hyaluronic acid concentration was found to be positively associated with progression of Kellgren/Lawrence grade in knees with and without OA (31).…”
Section: Discussionsupporting
confidence: 56%
“…Several serum biomarkers are known to be correlated with OA incidence and progression and have thus been proposed as diagnostic and prognostic markers for knee OA (28)(29)(30)(31). Serum hyaluronic acid concentration was found to be positively associated with progression of Kellgren/Lawrence grade in knees with and without OA (31). Serum concentration of keratan sulfate was suggested to be a potential marker of cartilage destruction (32).…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have reported that measuring sHA level may be useful for not only diagnosing knee OA but also identifying disease duration, severity, and the extent of OA-related knee pain. Therefore, sHA may have potential as a prognostic indicator of progressive knee OA, but the relationship between sHA and knee OA has only been examined in a few longitudinal studies [4,6,7] . Hyaluronan, also known as Hyaluronic acid (HA) or hyaluronate is a large linear non-sulfated glycosaminoglycan (GAG) with a molecular weight between10/6 and 10/7 Da.…”
Section: Introductionmentioning
confidence: 99%
“…OA should be diagnosed as soon as possible to begin treatment but the current diagnostic tools are inadequate to pick up preclinical changes. The gold standard method of diagnosis has long been plain radiography, but the sensitivity and specificity of that technique have been questioned [4] . However, when radiological diagnosis is established, significant joint damage has often already occurred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation